Embodiment and Corporeal Knowing in the Poetry of Gabeba Baderoon. Issue 2 (2nd July 2016) - Nortjé, Elizabeth Louise; Terblanche, Etienne
Abstract : In light of the regained interest in the body and embodiment in literary studies, this article seeks to elucidate the relationship between embodiment and knowing as evident in a number of poems by South African poet Gabeba Baderoon, a poet who has to date been neglected by critical inquiry. The purpose of this discussion is to illustrate the notion of embodiment depicted in Baderoon's work, and to indicate how her unique portrayal can contribute to the discourse on embodiment in literature. This paper takes a phenomenological approach of the kind entertained by Maurice Merleau-Ponty as its starting point, and utilises brief close readings of four of Baderoon's poems to demonstrate how the notion of embodiment can be understood through her work. It shall be argued that this is done on two interrelated and often simultaneously rendered levels: embodiment as a motif, and her poetry as a form of embodiment. This aspect of her work is especially lucid when considering the recurring theme of knowledge, in which she emphasizes the necessary embodiment in the process of knowing, an approach that transcends the presupposed mind-body dichotomy, and significantly relates to phenomenological notions such as 'lived experience' and 'dwelling'. Studying Baderoon's poems in light of her depiction of the body and embodiment not only offers a distinctive view of the embodied nature of knowledge, but moreover, provides an insightful glance at practising a 'theory' of embodiment in literary studies.